Implementasi Metode Sequential Searching pada Aplikasi “RUMAH KUCING PASIFIK” Berbasis Mobile - Rio Kurniawan; Pacipika Mahardika Putra (Institut Informatika dan Bisnis Darmajaya, 2021)
Cats are one of the pet mammals, but the difficulty of finding information in caring for and finding a cat is a priority problem for adopters or potential adopters. Therefore, it needs an application that contains a cat search feature to enclose information on caring for a given pet cat “rumah kucing pasifik” in an application.“rumah kucing pasifik” application implemented the sequential searching algorithm as a process of searching for cat data based on location data as search keywords. Software development used the prototype method which included designing a modelling system using the unified model language, interface design, coding and testing using the java programming language and using the firebase database.This application eased to find independent cats for adoption and cat tracking services. The system built still had many shortcomings. Therefore, it still needed improvement and development for further research, such as adding keywords based on cat gender and cat breed.Keywords: Search, Cat Animal